2005
DOI: 10.4321/s0365-66912005001000004
|View full text |Cite
|
Sign up to set email alerts
|

Comparación de tres métodos de inducción del incremento crónico de la presión intraocular en el cerdo (glaucoma experimental)

Abstract: Cauterization of the episcleral veins resulted in a significant and sustained elevation of the IOP and RGC loss when compared with the other two approaches tested in the present study, which barely modified the pig's RGC distribution. Thus, we conclude that the episcleral vein cauterization is the best of the methods tested to induce experimental glaucoma in the pig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Cell viability can be dramatically compromised by hypoxic stress [24, 47] and we found that the dorsal-periphery of the retina was the area where the RGCs are more vulnerable to hypoxia, even though significant differences were not found. This is consistent with the early events that take place in glaucoma, a neurodegenerative disease caused by elevated intraocular pressure (IOP) that possible causes mild hypoxia [48, 49] and where peripheral RGCs are more sensitive to damage, in accordance with others studies in pigs [5052], rats [50, 53] and mice [54]. …”
Section: Discussionsupporting
confidence: 88%
“…Cell viability can be dramatically compromised by hypoxic stress [24, 47] and we found that the dorsal-periphery of the retina was the area where the RGCs are more vulnerable to hypoxia, even though significant differences were not found. This is consistent with the early events that take place in glaucoma, a neurodegenerative disease caused by elevated intraocular pressure (IOP) that possible causes mild hypoxia [48, 49] and where peripheral RGCs are more sensitive to damage, in accordance with others studies in pigs [5052], rats [50, 53] and mice [54]. …”
Section: Discussionsupporting
confidence: 88%
“…One phenomenon that precedes cell death, already reported in neurons, is increased cell size, 15 and this has been reported to occur in glaucoma, 8,9,11,12 as well as in the early stages of damage to peripheral RGCs 1,16–18 . Previous studies by our group have analysed the degree of RGC neuroprotection mediated by BMD 3 months after IOP elevation.…”
Section: Introductionmentioning
confidence: 78%
“…The number and size of the RGCs in each retinal zone was compared between glaucoma eyes (left) and control eyes (right), as reported elsewhere. 9,[16][17][18]…”
Section: Retrograde Labelling Of Rgcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of the primate model is that the monkeys have eyes with similar anatomical characteristics to humans. Although monkeys are excellent animal models for studying human disease, there are several limitations to use monkeys, including ethical and economic factors [ 30 , 31 ]. Laser photocoagulation requires expensive ophthalmic equipment and highly specialized techniques.…”
Section: In Vivo Glaucoma Modelsmentioning
confidence: 99%